Severe congenital neutropenia caused by the elane gene mutation in a 4-year-old Vietnamese girl - Quan, Ho Dang; Phu, Nguyen Manh; Chi, Phan Thi Bich; Tho, Nguyen Huu; Thinh, Tran Cong Quoc (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Severe congenital neutropenia (SCN) is an exceptionally rare genetic disorder associated with life-threatening bacterial infections. Among the several genetic variations related to SCN, heterozygous mutations in the ELANE gene encoding neutrophil elastase account for approximately 40 - 55% of the genetic causes. Herein, we present the first documented case of SCN in a Vietnamese girl from the Central region of Vietnam. The diagnosis was confirmed through genetic analysis of the ELANE gene, a known causative gene in SCN. The patient exhibited severe neutropenia and a history of recurrent infections that did not respond well to treatment. Treatment involved the administration of granulocyte-stimulating factor (G-CSF) and antibiotics, resulting in a successful increase in neutrophil counts. This report contributes to the understanding of SCN’s clinical presentation, diagnosis, and management, particularly in regions with limited documented cases.